International Cooperation for Enhancing Nuclear Safety, Security, Safeguards and Non-proliferation Proceedings of the XXI Edoardo Amaldi Conference, Accademia Nazionale dei Lincei, Rome, Italy, October 7-8, 2019 - Maiani, Luciano; Jeanloz, Raymond; Lowenthal, Micah; Plastino, Wolfango (Springer Proceedings in Physics,, 2020)
This open access book examines key aspects of international cooperation to enhance nuclear safety, security, safeguards, and nonproliferation, thereby assisting in development and maintenance of the verification regime and fostering progress toward a nuclear weapon-free world. Current challenges are discussed and attempts made to identify possible solutions and future improvements, considering scientific developments that have the potential to increase the effectiveness of implementation of international regimes, particularly in critical areas, technology foresight, and the ongoing evaluation of current capabilities.